Assessment of the satisfaction with public health insurance programs by patients with chronic diseases in China: a structural equation modeling approach - Jinsong Geng; Xiaowei Chen; Jianwei Shi; Haini Bao; Qian Chen; Hao Yu (BMC, 2021)
Abstract Background China has successfully sustained its universal health insurance coverage over the past decade. Although patient satisfaction has been recognized as an important indicator to measure the performance of insurance programs in China, there is a lack of evidence on how patients with chronic diseases are satisfied with China's public health insurance programs and whether their satisfaction differs by type of insurance. We aimed to fill the evidence gap. Methods We established a hypothetical model that comprised patients' awareness of insurance policies, the fulfillment of patients' expectations of insurance benefits, patients' perceived value of health insurance coverage, patients' satisfaction with health insurance programs, patients' complaints, and trust in health insurance programs. We performed a confirmatory factor analysis by using a structural equation modeling (SEM) approach to examine the hypothesized model. A model-testing survey in 10 tertiary hospitals was conducted between June and October 2018, with a valid sample of 922 insured patients with chronic diseases. Results The SEM model, with good fit indices, showed that patients' awareness of health insurance policies, insurance program's fulfillment of expectations, and patients' perceived value of insurance coverage, positively predicted patient satisfaction (P < 0.01). The fulfillment of patients' expectations of insurance benefits was the major predictor of satisfaction with health insurance (coefficient = 0.593, P < 0.001), while the patients' perceived value of insurance coverage had the largest impact on their trust in health insurance (coefficient = 0.409, P < 0.01). Compared to patients with Urban-Rural Resident Basic Medical Insurance, Urban Employee Basic Medical Insurance enrollees had a higher degree of satisfaction with insurance on average (P < 0.01). Despite differences in the degree of satisfaction, the main findings from the SEM were also proved by the multi-group analysis. Conclusions Our findings highlight the importance of incorporating patients' perceived value as part of the ongoing efforts to increase satisfaction with health insurance by patients, especially those who have chronic diseases. Policymakers are also suggested to formulate evidence-informed reimbursement policies that meet patients' expectations.